Peningkatan Kemampuan Berhitung 1-20 Melalui Penggunaan Media Corong Berhitung pada Siswa Kelompok B1 Taman Kanak-Kanak Muslimat Wonocolo Surabaya - Fajar Karuniawati; Mukhoiyaroh Mukhoiyaroh (Program Studi Pendidikan Islam Anak Usia Dini, UIN Sunan Ampel Surabaya, 2019)
This research is backgrounded by the low ability in counting 1-20 related to calculation and diminution. It is proven by the result of doing the enrichment exercises which was done by 20 students in a class but only 5 students who got BHS score (Berkembang Sesuai Harapan) in the indicator of mentioning calculation result. Therefore, the objective of this research is to know the use of funnel calculation media in order to increase the ability in counting 1-20 for the students of Kindergarten Muslimat Wonocolo Surabaya, and to know the raising ability in counting 1-20 by using the funnel calculation media related to calculation and diminution. The research design which is used in this research is action research by using Kurt Lewin model. It consists of pre-cycle, cycle I, cycle II and reflection. The participant of this research is 20 students of B-1 group at TK Muslimat Wonocolo Surabaya. The action research of Lewin Kurt model consists of 4 stages; planning, implementation, observation and reflection. The results of this research are: 1) The use of funnel calculation goes well in cycle I. It can be seen in the activity of the students which enthusiastic in using funnel calculation media. Besides, the observation result of the teachers and students get the score in the percentage of 63,09%. It also can be seen from the activity of the teachers and students which rises by getting the score of 79,76% with the increase in 6,65. 2) There is an increasing of the ability in calculating 1-20 which is proven by the raising of the score after using funnel calculating media in cycle I in amount of 63,74% and the cycle II in amount of 76,87% by the increasing in the percentage of 13,13.